(untitled) (Politeja, 2023)
DIRECT DEMOCRACY IN AUSTRIA – PRACTICE AND DEVELOPMENT PROSPECTS First, the article traces the historical development of and legal regulations related to the instruments of direct democracy in the Second Republic. It details such forms of direct democracy as: the obligatory and optional referendum (Volksabstimmung), consultative referendum (Volksbefragung) and popular legislative initiative (Volksbegehren), as well as provides historical examples of their use. The latter part of the article elaborates on the positions of the main political parties in Austria and federal coalition plans for the years 2003-2020 against the backdrop of popularisation of forms of direct democracy. The research hypothesis adopted assumes that there is no agreement among the Austrian establishment as to whether direct democracy should become a permanent and significant supplement to representative democracy. The scarce interest in referendums and non-binding (consultative) referendums in Austria results from institutional and legal barriers, which make it difficult to initiate any forms of direct democracy, as well as from the huge influence of political parties that support representative democracy.